2010
DOI: 10.1259/bjr/24009651
|View full text |Cite
|
Sign up to set email alerts
|

MRI appearance of the pancreas in patients with cystic fibrosis: a comparison of pancreas volume in diabetic and non-diabetic patients

Abstract: ABSTRACT. We investigated differences in the volume of the pancreas in cystic fibrosis (CF) patients with and without diabetes using MRI to study the natural history of CFrelated diabetes (CFRD). We investigated 29 pancreas-insufficient adult CF patients, 13 with CFRD and 16 without diabetes. Patients with CFRD were receiving insulin therapy at the time of study. None of the non-diabetic CF patients had evidence of impaired glucose tolerance. Pancreas volume was estimated by MRI scans using T 1 weighted fatsup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…Smaller pancreata in patients with T1D have been reported by several groups [4•, 5, 3437]. The autopsy findings were corroborated by radiographic studies using US, CT, and MRI of the pancreas [5, 31, 3842]. Taken collectively, autopsy weights and clinical imaging studies show pancreatic weights or volumes are reduced by 20–50 % in children and adults with T1D compared to nondiabetic controls.…”
Section: Abnormal Pancreatic Exocrine Anatomy and Histology In T1dsupporting
confidence: 63%
See 1 more Smart Citation
“…Smaller pancreata in patients with T1D have been reported by several groups [4•, 5, 3437]. The autopsy findings were corroborated by radiographic studies using US, CT, and MRI of the pancreas [5, 31, 3842]. Taken collectively, autopsy weights and clinical imaging studies show pancreatic weights or volumes are reduced by 20–50 % in children and adults with T1D compared to nondiabetic controls.…”
Section: Abnormal Pancreatic Exocrine Anatomy and Histology In T1dsupporting
confidence: 63%
“…It is now evident that exocrine function and morphology should be evaluated in patients with diabetes, at least at the time of diagnosis. Imaging techniques like ultrasound (US), computerized tomography (CT), and magnetic resonance imaging (MRI) can greatly facilitate the assessment of the pancreas and correlate volume with exocrine function [2931]. …”
Section: Abnormal Pancreatic Exocrine Function In T1dmentioning
confidence: 99%
“…A number of previous studies have reported the lack of association between pancreatic volume and function. Sequeiros et al . described a group of nondiabetic cystic fibrosis patients with very small pancreatic size and suggested that sufficient insulin production only requires very small amounts of β‐cell mass.…”
Section: Discussionmentioning
confidence: 99%
“…The interstitial pools of zymogen elicit an inflammatory response, with eventual loss of exocrine tissue and replacement by connective tissue . The destruction of the pancreas can be so extensive, that in one study, 72% of patients imaged with magnetic resonance imaging did not have a pancreas detected as an anatomical entity …”
Section: Pancreatic Manifestations Of Cystic Fibrosismentioning
confidence: 99%